Caribbean Report 02-01-1998 - Thomas, Moya (anchor); Gordon, Orin (correspondent); Stern, Vivien (interviewee); John, Velon (interviewee); Prescod, John (interviewee); Burgess, Jacquie (interviewee); Singh, Wendy (interviewee); Simmons, David (interviewee) (The British Broadcasting Corporation, 1998)
This special edition of Caribbean Report examines penal reforms in the Caribbean. The region's prisons are in crisis as they face a myriad of problems including overcrowding, riots, violence and aged infrastructure. Vivien Stern, Penal Reform International (PRI) comments on whether these challenges are peculiar to the Caribbean. Jacquie Burgess of Caribbean Association for Feminist Research and Action (CAFRA) speaks on women in the region's prisons. Velon John of St. Lucia and Barbados' Attorney General David Simmons, proponents of capital punishment, comment on issue of hanging and the Caribbean Court of Appeal.
1. Special report by Moya Thomas (00:00-00:26)
2. Across the Caribbean, alarm bells have been ringing on the region's penal system (00:27-02:21)
3. Vivien Stern comments on whether the rest of the world experience similar crises (02:22-04:04)
4. Velon John reports on the prison conditions in St. Lucia (04:05-05:50)
Keywords: Prisons -- Guyana; Prisons -- Jamaica; Prisons -- Saint Lucia; Prisoners -- Caribbean Area; Criminals -- Rehabilitation; Punishment -- Social aspects; Women prisoners -- Caribbean Area; Prisons -- Overcrowding; Prison violence; Imprisonment -- Caribbean Area; Community-based corrections; Capital punishment -- Caribbean Area; Appellate courts -- Caribbean Area